Construção de uma veículo aéreo não tripulado na configuração quadrirrotor como plataforma de estudos - Queiroz, Juliano da Rocha (2014)
This paper reports the construction process of a quadrotor unmanned air vehicle, as a platform of control techniques research. The quadrotor is an aircraft whose movement is provided by four engines installed in a cross-shaped struct, capable of vertical takeoff and landing. The main objectives of the project were: the platform construction; obtaining a mathematical model of the vehicle; analysis and design of PID controllers for the stabilization of the aircraft; and developing a graphical interface in La bVIEW. As a result, the transfer function was obtained in the frequency domain, related to the angular dynamics of the axes, from the second Newton’s law for rigid bodies with six degrees of freedom, where was considered the system symmetry and ignored thegyroscopic effect. After analyzing the functions, it was developed an embedded PID controller in the Arduino device for each angle of the vehicle, and a graphical interface through which one can update in real time the controller gains, as well as view th e quadrotor parameters such as angle, angular speed, engine speed, among others.